A new approach for the preparation of well-defined Rh and Pt nanoparticles stabilized by phosphine-functionalized silica for selective hydrogenation reactions. Issue 22 (6th March 2017) - Llop Castelbou, J.; Szeto, K. C.; Barakat, W.; Merle, N.; Godard, C.; Taoufik, M.; Claver, C.
Abstract : A new methodology is reported for the synthesis of well defined silica-supported metallic nanoparticles that are selective hydrogenation catalysts. Abstract : In this work, a new methodology for the synthesis of well-defined metallic nanoparticles supported on silica is described. This methodology is based on the surface control provided by SOMC. The nanoparticles are formed via the organometallic approach and are catalytically active in the hydrogenation of p -xylene, 3-hexyne, 4-phenyl-2 butanone, benzaldehyde, and furfural.